KONSENTRASI DAN INTEGRASI KEPEMILIKAN PADA INDUSTRI MEDIA INTERNASIONAL DALAM PERANG FORMAT HIGH DEFINITION OPTICAL DISK - Fanani, Fajriannoor (Jurnal The Messenger, 2016)
High definition technology development in the entertainment industry, especially film industry, has produce classic problem about format consensus in the media industry. This situation eventually creates the so called war of format between the two most popular high definition formats, the Blu-ray from Sony/Hitachi and the HD DVD from Toshiba. Unlike the war of format before, for example is VHS versus Betamax war, that determinated mostly by the consumer, the format war between Blu-ray and HD DVD is strongly affect by the abilities of the companies behind the two format to consentrate and integrate their business moghul and also to make alliance between competitiors. Concentration of ownership is appears in the trend of holywood studios to merge with the bigger studios, which is creates a few conglomeration in the movie business. Integrations of business could be seen from the owners of the big studios that not only have the studios, but also many other business that relate or not with the entertainment business. And least, the alliance could be seen from this big studios alliance to support one of the format. Initially the HD DVD was on the fruitfull position because has been back up by the studios like Warner Bros, Paramount, and Universal that have more market share in US that the studios that support Blu-ray format, which is Sony, Walt Disneym and 20th Century Fox. Fortunately for Blu-ray, Sony already sells millions of PS 3 console that ingeniously could read Blu-ray disk; this means there s already millions of Blu-ray reader device in the hand of consument, something that Toshiba could not generate. In the end, the victory of Blu-ray format is accelerate by the switching side of Warner Brothers studio to the Blu-ray follow by the others big studios. Conclusively, the success of a new technology, especially the media industry, is sometimes not depends on the quality of the technology itself. Often, the success is determined by the availability of the industries that support the technology. The war of format between HD DVD and Blu-ray definitely show the determination of media industry in the development of new technology.